Assessing Socio-ecological Systems Using Social Media Data: An Approach for Forested Landscapes in Tierra del Fuego, Argentina - Huertas Herrera, Alejandro; Toro Manriquez, Monica; Soler, Rosina; Lorenzo, Cristian; Lencinas, Maria Vanessa; Martinez Pastur, Guillermo (My University, 2021)
The purpose of this study was to analyse how visitors valued a socio-ecological system through the use of social media data. We gathered YouTube ' s videos of Ushuaia city and its surrounding forested landscapes (Tierra del Fuego, Argentina) posted between 2010 and 2020. We used the screen time (seconds) of each video to compare the value of visitors on biophysical, cultural, and biodiversity attributes of the studied socio-ecological system. Each of the visitors registered differently the same attribute (e.g. mountains, forests, signposts, fauna, among others), therefore we assessed the time each visitor spend on any attribute, that was calculated considering the focus and scale through which it was observed. Based on our analyses, we found a diversity of attributes with different valuation data for each visitor. Attributes were classified as biophysical, cultural, and biodiversity variables, and the origin of the visitors (e.g. regions of the world) was also evaluated, with descriptive and multivariate analyses. Results indicated that visitors give more value to biophysical and cultural attributes compared to local biodiversity. These outputs highlight the need to explore and implement alternative methods to assess the socio-ecological values to achieve management objectives, and to include socio-ecological attributes in the study area as key indicators to create better tools and solutions for conservation issues. In this context, we provide a new insight into how visitors can appreciate different socio-ecological values.
Keywords: youtube; screen time; visitor attitudes; social realities; sustainable development; world’; s regions